Sofosbuvir in combination with daclatasvir or simeprevir for 12 weeks in noncirrhotic subjects chronically infected with hepatitis C virus genotype 1: a randomized clinical trial - Pott-Junior, H.; Bricks, G.; Grandi, G.; Figueiredo Senise, J.; Castelo Filho, A. (Clinical microbiology and infection, 2019)
To investigate the efficacy and safety of sofosbuvir (SOF) plus daclatasvir (DCV) or simeprevir (SMV) in a randomized, open-label, noninferiority trial of patients infected with hepatitis C virus genotype 1, who were previously unresponsive to pegylated interferon and ribavirin or were treatment naive. Patients were randomly assigned to receive SOF (400 mg once daily) plus DCV (60 mg once daily) or SMV (150 mg once daily) for 12 weeks. The analysis included all participants who received at least one dose of the study drugs. The primary endpoint was sustained virologic response 12 weeks after ending treatment (SVR12; hepatitis C virus RNA measured using COBAS TaqMan RT-PCR (lower limit of detection and quantification of 12 UI/mL)). This study was registered at ClinicalTrials.gov (NCT02624063). A total of 125 of 127 enrolled and randomized patients started treatment (n = 65 SOF + DCV; n = 60 SOF + SMV). SVR12 was attained in 121 patients (96.8%): 65 (100%) receiving SOF + DCV (95% confidence interval (CI), 94.5 to 100) and 56 (93.3%) receiving SOF + SMV (95% CI, 83.8 to 98.2; absolute difference, 6.6%; 95% CI, −15.0 to 0). The most common adverse events were fatigue (n = 32, 25.6%), headache (n = 27, 21.6%), and mood swings (n = 24, 19.2%). No patients discontinued therapy. The overall SVR rate was 96.9%; SOF + DCV (100%) was higher than that of SOF + SMV (93.3%). Despite no statistically significant intergroup difference in SVR12 rates, the noninferiority of SOF + SMV to SOF + DCV could not be established because the difference in efficacy was clinically relevant.